An early European experience with transapical off-pump mitral valve repair with NeoChord implantation. (5th March 2018) - Colli, Andrea; Manzan, Erica; Aidietis, Audrius; Rucinskas, Kestutis; Bizzotto, Eleonora; Besola, Laura; Pradegan, Nicola; Pittarello, Demetrio; Janusauskas, Vilius; Zakarkaite, Diana; Drasutiene, Agne; Lipnevicius, Arturas; et al.
Abstract: OBJECTIVES: Transapical off-pump NeoChord repair is a novel minimally invasive surgical procedure to treat degenerative mitral valve regurgitation. The aim was to evaluate 1-year clinical results of the NeoChord procedure in a consecutive cohort of patients. METHODS: Between February 2013 and July 2016, 213 patients were enrolled in the NeoChord Independent International Registry. All patients presented severe mitral regurgitation due to flail/prolapse of 1 or both leaflets, and they all completed postoperative echocardiographic assessment up to 1 year. We identified the primary end point as composed of procedural success, freedom from mortality, stroke, reintervention, recurrence of severe mitral regurgitation, rehospitalization and decrease of at least 1 New York Heart Association functional class at 1-year follow-up. We also compared outcomes according to the anatomical classification (Type A: isolated central posterior leaflet disease; Type B: posterior multisegment disease; Type C: anterior, bileaflet, paracommissural disease with/without leaflet/annular calcifications). RESULTS: The median age was 68 years (interquartile range 56–77), and the median EuroSCORE II was 1.05% (interquartile range 0.67–1.76). The number of Type A, B and C patients was 82 (38.5%), 98 (46%) and 33 (15.5%), respectively. Procedural success was achieved in 206 (96.7%) patients. At 1-year follow-up, overall survival was 98 ± 1%. Composite end point was achieved in 84 ± 2.5% for the overall population and 94 ± 2.6%, 82.6 ± 3.8% and 63.6 ± 8.4% in Type A, Type B and Type C patients, respectively ( P < 0.0001). CONCLUSIONS: These results demonstrate that the NeoChord procedure is safe, effective and reproducible. Clinical and echocardiographic efficacy is maintained up to 1 year with significant differences among the anatomical groups. Specific anatomical selection criteria are necessary to achieve stable results.